Pengaruh Permainan Edukatif Berbasis Power Point Terhadap Kemampuan Berbahasa Pada Anak Kelompok B di TK Telkom 2 Palembang Tahun 2023 - Khotimah, Alfina Khusnul; Sari, Mardiana; Ahmad, Syarwani (Jurnal Ilmiah Wahana Pendidikan, 2023)
Abstract This study aims to find out whether educational games based on power point can affect the reading ability of group B children in Kindergarten Telkom 2 Palembang. Research using a quantitative approach to the experimental method. The type of design used is the One-Group Pretest-Posttest Design which was carried out for 8 meetings, 1 time pretest, 6 times treatment, 1 time posttest. The subjects in this study were the children of group B TK Telkom 2 Palembang, totaling 10 children. The results of the study after being given treatment using educational games based on power point showed that the average score during the pretest was 21.50 and the posttest was 38.70, meaning that the average posttest score was greater. Based on data analysis using the SPSS version 26 program with paired samples t-test, the result is a significant value of 0.000 < 0.05 so that H0 is rejected and Ha is accepted. So it can be concluded that educational games based on power point affect the reading ability of group B children at TK Telkom 2 Palembang. reading skills, power point based, educational games